Frequency of Common Causes of Severe Anemia in Children under 5 Years of Age Admitted in Children Hospital, Lahore - Rubab Hafeez, Sadia Amir, Ammara Sardar, Nagham Nawaz Awan, Madiha Jameel, Sumbal Abbas, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of common causes of severe anemia in children under 5 years of age admitted in children hospital, Lahore Design of the Study: Cross sectional study Study Settings: The study was conducted at Department of Pediatric Medicine, Children Hospital, Lahore from 5 Sep 2018 to 5 March 2019. Material and Methods: Patients were evaluated for the severity of anemia by the Hb level, baseline investigations, CBC with peripheral film and retics count, Hb electrophoresis, osmotic fragility test, G6PD assay, serum bilirubin, coomb’s test and bone marrow biopsy ,if required. The demographic characteristics of patients and WHO criteria for Hb level was noted on the specifically designed study proforma. A blood sample was drawn and was sent to hospital laboratory for analysis of related causes of severe anemia. The collected data was entered and analyzed using SPSS software version 17.0. Results of the Study: The mean age of patients was 30.41 ± 18.60 months with minimum and maximum age as 1 and 60 months. There were 169(46.3%) boys and 196(53.7%) girls with slightly higher female to male ratio. The mean Hb level was 5.15 ± 1.06 g/dL with minimum and maximum Hb as 3.40 and 6.90 g/dL. The common causes of anemia were assessed that showed 232(63.6%) patients had iron deficiency, 7(1.9%) cases had Sickle cell anemia, 37(10.1%) cases had Septicemia and 89(24.4%) cases had malaria Conclusion: According to the findings of current study, the common causes of severe anemia in local children are found to be, iron deficiency anemia in 232(63.6%) cases, Sickle cell anemia in7(1.9%) cases ,septicemia in 37(10.1% ) cases and malaria in 89(24.4%) cases. So during clinical evaluation of patients it must be kept in mind that these factors can contribute to severe anemia. So, preventive and therapeutic strategies must be ensured to minimize the risk of severe anemia in these children